2015
DOI: 10.3389/fmicb.2015.01325
|View full text |Cite
|
Sign up to set email alerts
|

Natural Sunlight Shapes Crude Oil-Degrading Bacterial Communities in Northern Gulf of Mexico Surface Waters

Abstract: Following the Deepwater Horizon (DWH) spill in 2010, an enormous amount of oil was observed in the deep and surface waters of the northern Gulf of Mexico. Surface waters are characterized by intense sunlight and high temperature during summer. While the oil-degrading bacterial communities in the deep-sea plume have been widely investigated, the effect of natural sunlight on those in oil polluted surface waters remains unexplored to date. In this study, we incubated surface water from the DWH site with amendmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 104 publications
3
73
0
Order By: Relevance
“…Incubation of seawater with oil (lightsweet crude) in sunlight resulted in changes in microbial community structure and reduced bacterial diversity (Bacosa et al, 2015). Sunlight-selected phylotypes from laboratory studies were consistent with microbial communities found in mousse from the Deepwater Horizon spill, suggesting that sunlight influences pollutant fate through impacts on microbial communities.…”
Section: Photodegradationmentioning
confidence: 61%
“…Incubation of seawater with oil (lightsweet crude) in sunlight resulted in changes in microbial community structure and reduced bacterial diversity (Bacosa et al, 2015). Sunlight-selected phylotypes from laboratory studies were consistent with microbial communities found in mousse from the Deepwater Horizon spill, suggesting that sunlight influences pollutant fate through impacts on microbial communities.…”
Section: Photodegradationmentioning
confidence: 61%
“…Cycloclasticus , a known PAH degrader (Dyksterhouse et al, 1995; Geiselbrecht et al, 1998), dominated on day 50 in 4°C incubations (35–43%), but nearly undetectable in controls and in 24°C treatments ( Figure 4B ). Alcanivorax , a known alkane degrader (Bacosa et al, 2015b, 2016), developed from undetectable to 5–7% with oil addition at both temperatures, but not in controls. In the presence of oil, Alteromonas increased from 1% initially to 4–11% on days 5 and 12 in surface water, but particularly dominated using bottom water (15–34%), suggesting the importance of water chemistry in controlling their development.…”
Section: Resultsmentioning
confidence: 99%
“…Non-metric multidimensional scaling (NMDS) was used to examine the overall patterns of bacterial community structure using Hellinger-transformed relative abundances of bacterial genera (Bacosa et al, 2015b). NMDS was performed using Bray-Curtis dissimilarity distances in PAST software package, V2.17 (Hammer et al, 2001).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations